Recycling of vehicles: Russian realities and foreign experience - M. E. Semerikova; T. V. Naumova (Научный вестник МГТУ ГА, 2025)
The handling of decommissioned aircraft is a relatively new problem for national civil aviation. For many decades, the global experience has been dominated by the practice of placing them in open areas, the so-called cemeteries of aircraft. At the same time, the increasing requirements for environmental protection force the introduction of environmentally sound forms of activity at all stages of the life cycle of a technical device, including at the final stage – disassembly and disposal. It has been revealed that in Russia there is no orderly system for handling the aviation equipment in the post-operational period of its life cycle. However, there is a need for such a system, and it will increase, since the “Comprehensive Program for the Development of the Air Transport Industry of the Russian Federation until 2030” assumes the gradual withdrawal of foreign-made aircraft from the airline fleet under Western sanctions. In the course of the study, an overview of the regulatory and legal support for recycling processes in Russian automobile, railway and marine transport has been carried out; the activities of Russian companies engaged in the disposal of aviation equipment have been analyzed and contradictions in the market of recycling services have been revealed; tools for stimulating recycling are proposed for vehicle owners; foreign experience is studied and summarized, in particular, the PAMELA and Airbus Lifecycle Services projects of Airbus Corporation, the activities of the AFRA association of Boeing Corporation, the Falcon Aircraft Recycling project of Emirates, the international project Airbus China.